(untitled) (Experimental biology, 2025)
According to the requirements of the State Pharmacopoeia of the Republic of Kazakhstan for the control of medicinal products, one of the essential components in ensuring the safety, efficacy, and high quality of pharmaceutical products manufactured in the country is the assessment of their antimicrobial activity. Compliance with microbiological purity standards enables a comprehensive evaluation of drug quality, strengthens the alignment of domestic pharmaceutical production with international standards, and contributes to maintaining competitiveness in the pharmaceutical market. This study experimentally investigated the antimicrobial activity of the pharmaceutical substance and finished dosage form of Captopril produced in Kazakhstan against pharmacopoeial test microorganisms, including Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Candida albicans and Aspergillus brasiliensis. It is known that certain medicinal products may possess intrinsic inhibitory activity, which can distort microbiological test results and lead to false-negative outcomes. Therefore, preliminary assessment of a drug’s impact on microbial growth is a critical step for accurate microbiological evaluation. Three batches of Captopril substance and three batches of the tablet dosage form were examined. The results demonstrated that dilutions of 1:10 and 1:20 exhibited a pronounced inhibitory effect against E. coli, S. aureus and B. subtilis. No activity was observed against Candida albicans, Aspergillus brasiliensis or P. aeruginosa, while the 1:50 dilution completely lacked antimicrobial activity. The findings confirm the importance of employing methodologies fully compliant with pharmacopoeial requirements when assessing the quality of Captopril substance and its finished dosage form. Moreover, the results justify the necessity of including information on the drug’s intrinsic antimicrobial properties in the manufacturer’s specification. This study holds practical significance for ensuring the quality and safety of domestically produced pharmaceutical products.